The application of strategic management in a public healthcare service system / Luo Jiaxiang, Fadilah Puteh and Sarina Othman - Luo, Jiaxiang; Puteh, Fadilah; Othman, Sarina (2023)
The financial operating condition of a public hospital is directly associated with developing healthcare services. When the operating environment changes completely, financial management is a key driver in hospital management, and its importance is self-evident. A public hospital needs to make scientific decisions in the face of current healthcare reform, optimising business processes and reducing operating costs. These measures are directly related to the financial management in the hospital. This paper is on the premise of public hospital reform, initially following the rules and regulations of hospital financial management.